LOFTUSIA CF. ANATOLICA HORIZON IN UPPER MAASTRICHTIAN LIMESTONES OF THE EASTERN GREECE PLATFORM (MOUNT PTOON, BOEOTIA, GREECE): PALAEOBIOGEOGRAPHICAL REMARKS - Zambetakis - Lekkas, A.; Kemeridou, A. (Bulletin of the Geological Society of Greece, 2018)
Researches on upper Cretaceous limestones from the Eastern Greece platform in the area between Kokkinon and Akrefnion (Boeotia, Greece) revealed the presence of a horizon rich in Loftusia cf. anatolica (foraminifer). In this horizon, of late Maastrichtian age, L. cf. anatolica is associated with debris of Rudists, Orbitoides media, O. apiculata, O. gensacicus, Siderolites calcitrapoides, Omphalocyclus macroporus, Hellenocyclina beotica, Miliolidae, Dasycladaceae and echinoderms. It is found in an undisturbed sequence of limestones, where both the underlying and the overlying horizons are of the same facies and contain debris of Rudists, Hellenocyclina beotica, Orbitoides media, Siderolites calcitrapoides, Sulcoperculina sp., Rotaliidae, Mélobesiées,Nummofallotia sp., echinoderms. L. cf. anatolica is confined in the above mentioned horizon and it is found neither in the underlying nor in the overlying beds. This fades reflects an outer shelf environment in front of the rudist reefs. It is the first time that this species is reported in situ in Greece in an undisturbed stratigraphie sequence of upper Cretaceous limestones up to Paleocene flysch.